2019
DOI: 10.1111/sms.13412
|View full text |Cite
|
Sign up to set email alerts
|

Motor competence, perceived physical competence, physical fitness, and physical activity within Finnish children

Abstract: The purpose of this study was to investigate reciprocal relationships among students’ motor competence (MC) (leaping, throwing, catching, jumping skills), perceived physical competence, health‐related fitness (HRF) (20 m shuttle run, push‐up, abdominal muscles endurance tests) and objectively measured moderate‐to‐vigorous physical activity (MVPA). Participants included 422 Grade 5 Finnish children (246 girls). Two separate structural equation models investigated paths (a) from MC through both perceived physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 38 publications
5
62
2
Order By: Relevance
“…13 The detailed description of the MC measurements is present in Table 1. 7 The scores of the MC tests were standardized, and analyses were performed using Z-scores.…”
Section: Motor Competencementioning
confidence: 99%
See 1 more Smart Citation
“…13 The detailed description of the MC measurements is present in Table 1. 7 The scores of the MC tests were standardized, and analyses were performed using Z-scores.…”
Section: Motor Competencementioning
confidence: 99%
“…Most of these variable-level associations have been supported empirically. 7 However, only two cluster analytic studies that applied a person-oriented strategy to address the individual differences in movement skills have examined the role of MC and PC on PA. 8,9 These studies identified different movement profiles within samples of children and also revealed that participants having high MC and PC also demonstrated higher levels of self-reported 8 and objectively measured PA engagement 9 than students having low MC and PC.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is taking exercise, people who exercise will tend to get further health benefits [6]. The influence of lack of motor skills and physical fitness facilities to improve health in children to adolescents also become one of the negative factors in the involvement of physical activity [9]. Physical activity has many types, most research is designed to increase motivation for physical activity focuses on sports behaviour and ignores sports participation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of these reviews, a growing number of longitudinal studies investigating the causal or reciprocal relationship between MC and PA, as well as the potential mediators of this relationship in childhood and adolescence, have been noted. [16][17][18][19][20] The results of the Copenhagen School Children Intervention Study 18 indicated a reciprocal relationship between MC and PA over 7 years from early to late childhood. The level of MC achieved in late childhood was predicted by PA in early childhood.…”
mentioning
confidence: 99%
“…18 In addition, crosssectional studies provided preliminary support for the reciprocal nature of the relationship between PA and MC, taking into account PMC or HRF. 16,21,22 In a study with older Finnish children, Jaakkola et al 16 tested the longitudinal association between MC and MVPA in both directions, including PMC and HRF as mediators. They interpreted their results as almost fully consistent with the Stodden et al 8 concept.…”
mentioning
confidence: 99%